Perengkahan Katalitik PalmFatty Acid Distillate (PFAD) Menghasilkan Biofuel Menggunakan Katalis Abu Tandan Kosong Sawit (TKS) Dengan Variasi Temperatur Dan Kecepatan Pengadukan - Sri Hidayanti; Yelmida Yelmida; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Ash of empty palm fruit bunches is the solid waste from process of making crude palm oil (CPO). Ash of empty palm fruit bunches have many component that make it can to be use as a catalyst. Palm fatty acid distillate (PFAD) is a byproduct from process of making cooking oil. PFAD potential to converted into biofuel with catalytic cracking process.  This study aims to utilize ash of empty fruit bunches and PFAD to be raw material of making biofuel, to know component of biofuel produced. Yield maximum biofuel obtained at a temperature of 410 0 C with  stirring speed 250 rpm that is equal to 57,14%. While the largest biofuel conversion obtained at stirring speed of 300 rpm and a temperature of 4100C in the amount of 50.671%.   Cracking results analyzed by GCMS and found the biofue produced more dominant is a constituent of gasoline fuel .  Keywords: Ash of empty palm fruit bunches, Biofuel, Catalytic Cracking, PFAD